If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
y = (-8/9)*x-(8/9) // - (-8/9)*x-(8/9)
y-((-8/9)*x)+8/9 = 0
(8/9)*x+y+8/9 = 0
8/9*x+y+8/9 = 0 // - y+8/9
8/9*x = -(y+8/9) // : 8/9
x = (-(y+8/9))/8/9
x = -9/8*(y+8/9)
x = -9/8*(y+8/9)
| -5+7x+7=8(x+3)-9 | | 12R=1/4M-5 | | 4x-28y=44 | | -2y+13=14-y | | g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 | | -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) | | 0=16t^2+138t+55 | | 6a+2a+12=7+6a+3 | | 4x-5+2x=13 | | y=4x^2-6x-7 | | 0=16t^2+138t+c | | x^2-y^2=50 | | x+8+5x=2-2x | | 2x^3+7x^2-15=0 | | 7.6x-1.6=13.6 | | 2k=56 | | m-7m+6=20 | | -5k+3=-6+4k | | 6(k-3)-7=6k-(5k-2) | | x^2-x^2-2+1=7 |